Analisis Yuridis Konflik Pernikahan dalam Hukum Adat dan Hukum Nasional Ditinjau dalam Pasal 18B Ayat (2) UUD 1945 - Dian Mentari Gobel; Wenny Almoravid Dungga; Mohamad Hidayat Muhtar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the regulation of marriage in the customary and national legal systems and the legal implications of Article 18B Paragraph 2 of the 1945 Constitution on marriage. Given that Indonesia has a diverse society and is rich in traditions, customary law operates concurrently with national law, often giving rise to conflict. The research method used is a normative approach with descriptive analysis. The results show that customary law and national law have different characteristics, where customary law is flexible and contextual, while national law prioritizes the principles of equality and individual protection. Constitutional Court Decision No. 46/PUU-VIII/2010 is a crucial point in recognizing the rights of children born outside of marriage, creating a bridge between customary and national legal norms, and emphasizing the importance of harmonization between the two. This study is expected to provide deeper insight into the need for policies that support collaboration between customary and national law in regulating marriage.